Connexin43 dephosphorylation at serine 282 is associated with connexin43-mediated cardiomyocyte apoptosis - Yang, Yutong (Cell Death Differ, 2019)
Gap junction protein connexin 43 (Cx43) plays an important role in regulating cardiomyocyte survival in addition to regulating electrical coordination. Cx43 dephosphorylation, found in severe cardiac pathologies, is thought to contribute to myocardial injury. However, the mechanisms underlying Cx43 mediation of cell survival and myocardial lesions remain unknown. Here, we found that transfecting an adenovirus carrying a mutant gene of Cx43-serine 282 substituted with alanine (S282A) into neonatal rat ventricular myocytes (NRVMs) induced cell apoptosis and Ca(2+) transient desynchronization, whereas using gap junction inhibitor or knocking down Cx43 expression with Cx43-miRNA caused uncoupled Ca(2+) signaling without cell death. Similarly, while Cx43-S282A(+/+) failed in generation, Cx43-S282A(+/−) mice exhibited cardiomyocyte apoptosis and ventricular arrhythmias dependent on S282 dephosphorylation. Further, Cx43 dephosphorylation at S282 activated p38 mitogen-activated protein kinase (p38 MAPK), factor-associated suicide and the caspase-8 apoptotic pathway by physically interacting with p38 MAPK. These findings uncovered a specific Cx43 phosphorylation residue involved in regulating cardiomyocyte homeostasis. S282 phosphorylation deficiency acts as a trigger inducing cardiomyocyte apoptosis and cardiac arrhythmias, providing a potential mechanism for Cx43-mediated myocardial injury in severe cardiac diseases.